Molecular Bases for Sensitivity to Tubulin-Binding Herbicides in Green Foxtail - Délye, Christophe (American Society of Plant Biologists, 2004)
We investigated the molecular bases for resistance to several classes of herbicides that bind tubulins in green foxtail (Setaria viridis L. Beauv.). We identified two α- and two β-tubulin genes in green foxtail. Sequence comparison between resistant and sensitive plants revealed two mutations, a leucine-to-phenylalanine change at position 136 and a threonine-to-isoleucine change at position 239, in the gene encoding α2-tubulin. Association of mutation at position 239 with herbicide resistance was demonstrated using near-isogenic lines derived from interspecific pairings between green foxtail and foxtail millet (Setaria italica L. Beauv.), and herbicide sensitivity bioassays combined with allele-specific PCR-mediated genotyping. Association of mutation at position 136 with herbicide resistance was demonstrated using herbicide sensitivity bioassays combined with allele-specific PCR-mediated genotyping. Both mutations were associated with recessive cross resistance to dinitroanilines and benzoic acids, no change in sensitivity to benzamides, and hypersensitivity to carbamates. Using three-dimensional modeling, we found that the two mutations are adjacent and located into a region involved in tubulin dimer-dimer contact. Comparison of three-dimensional α-tubulin models for organisms with contrasted sensitivity to tubulin-binding herbicides enabled us to propose that residue 253 and the vicinity of the side chain of residue 251 are critical determinants for the differences in herbicide sensitivity observed between organisms, and that positions 16, 24, 136, 239, 252, and 268 are involved in modulating sensitivity to these herbicides.